Regesten Kaiser Friedrichs III. (1440-1493) nach Archiven und Bibliotheken geordnet Die Urkunden und Briefe des Österreichischen Staatsarchivs in Wien, Abt. Haus-, Hof- und Staatsarchiv: Allgemeine Urkundenreihe, Familienurkunden und Abschriftensammlungen (1483-1488) - Gretzel, Peter (2014)
This volume of abstracts of charters Emperor Frederick´s III in the series Regesta Imperii focusses on the last decade of his rule, in particular on the years between 1483 and 1488. They are based on the original charters in the Allgemeine Urkundenreihe and Familienurkunden in the Haus-, Hof- und Staatsarchiv in Vienna and its collections of copies of those charters that have not come down to us in the original, all of which serve to illustrate a number of major historical aspects: Defension of hereditary territories against the Hungarian King Matthias Corvinus, consolidation of the empire in the West, the joint rule of the Emperor and his son Maximilian I.